HAZOP analysis of small-scale unit for biokerosene production from short-chain esters - Mota, Francisco de Assis da Silva; Oliveira, Amanda Lívia de; Leitão, Antônio Bruno de Vasconcelos; Medeiros, Nayara Cardoso de; Caselli, Francisco de Tarso Ribeiro (Brazilian Journal of Production Engineering, 2023)
With intense industrialization comes the need for more energy sources to supply this demand. With the awareness of the population and governments, the search for renewable energy sources, such as biofuels, is growing. Aviation biokerosene is an ideal substitute for petroleum-based kerosene and can be obtained through the transesterification process of animal or vegetable fat and alcohol. However, in industrial processes such as these, it can generate several risks that can compromise the health of the operator, equipment, production, and others. For this reason, the objective is to perform a risk analysis in a smallscale production unit of biokerosene for aviation, using the Hazop methodology, which separates the production unit into nodes, analyzing them separately. Thus, with identified risks, it is possible to find the causes, consequences, and best actions to avoid them. With this, it was observed that flow rate and temperature are the main parameters that influence this production unit, being necessary to study them in order to standardize the ideal loads of each equipment, and not to generate disturbances. Also, control equipment such as valves, pumps and piping should follow periodic maintenance